0022 Improving predicted effectiveness of shiftworkers in watchfloors. (25th May 2022) - Matsangas, Panagiotis; Shattuck, Nita; Sheehan, Sarah; Dotson, Elizabeth
Abstract: Introduction: In support of 24/7 hour operations around the globe, Navy and Marine Corps shore-based watchfloors provide information, intelligence, and technical support to the warfighter. Personnel working on these watchfloors are challenged to obtain consistent sleep due to shift working. The study objectives were to model the predicted effectiveness (PE) of the current watch schedule and recommend a new schedule to improve sleep, safety, and performance. Methods: In a 3-week longitudinal, naturalistic study, we assessed the work/rest patterns and well-being of watchstanders while on their typical watch schedule. Participants (N=11, age:19-33yrs) completed an online sleep/activity log for the study period. Standardized tools (Pittsburgh Sleep Quality Index--PSQI, Epworth Sleepiness Scale--ESS, Insomnia Severity Index--ISI, Profile of Mood States--POMS) were completed pre/post-study. Based on study findings combined with information gathered from the command leadership, we designed an improved watch schedule. The Fatigue Avoidance Scheduling Tool (version 3.3.01T) employing the Sleep, Activity, Fatigue, and Task Effectiveness model (SAFTE/FAST) was used to model PE in the legacy and newly improved watch schedules. Results: The median daily reported sleep duration was 6hrs (range: 5-8.5hrs). Nine participants (82%) were classified as poor sleepers and six (55%) had elevated daytime sleepiness. Four (36%) participants had moderately severe/severe insomnia symptoms. In terms of mood, 10 (91%) participants had a lower vigor-activity score than the adult norms, whereas eight (73%) scored higher than the adult norms for fatigue. The mid-shift watches had low PE that dropped steeply throughout the shift. The timing of low PE coincided with the period in which personnel was briefing leadership and/or commuting from work. Conclusion: Based on our findings, we recommended a schedule that enables more regular sleep patterns. Compared to the legacy schedule, the new schedule increased both the number of week days and weekend days off, with 2-3 full weekends off per month. Also, PE was improved and the trough in PE did not occur during the commute. Lastly, we recommended that the new watch schedule should rotate less frequently with longer times on an assigned shift. Support (If Any): This work was supported in part by the Naval Medical Research Center's Naval Advanced Medical Development Program.